Investigation on mechanical, microstructural and thermal properties of Sn-0.7Cu and Sn-1Ag 0.5Cu solder alloys bearing Fe and Bi / Mohammad Hossein Mahdavifard - Mohammad Hossein, Mahdavifard (2017)
Low-Ag Sn-Ag-Cu (SAC) alloys such as Sn-1 wt.%Ag-0.5 wt.% Cu (SAC105) have been considered as a solution to both the cost and poor drop impact reliability issues of high Ag SAC solders. Moreover, alloying elements have been added into SAC solder alloys to refine the microstructure, and improve the wettability and mechanical properties. In the present study, Fe and Bi were added together to the low Ag solder, Sn-1 wt.%Ag-0.5 wt.% Cu (SAC105), and without Ag, Sn-0.7Cu(SC07) to investigate the effect of these two elements on the bulk alloy microstructure, tensile and thermal properties. Fe and Bi have different role to improve reliability of solder alloy. Fe improve and stabilize mechanical properties and drop reliability, whereas Bi strengthen solder by solid solution effect, decrease melting temperature and improve wetting properties. On the basis of the previous works, 0.05wt%Fe added to SAC105 or SC07 because by increasing Fe more than 0.1wt% it makes large FeSn2 intermetallic in bulk of solder which deteriorate mechanical properties. Also, selected 1 and 2wt% Bi to add to SAC105 or SC07 because Liu et al. showed that more than 3wt% Bi make solder too brittle. Addition of Bi to SAC105-Fe and SC07-Fe increased yield strength and ultimate tensile strength while decreased total elongation. Bi degenerated the eutectic region into a chain-like arrangement, which decreased Cu6Sn5 and increased β-Sn in solder. 0.05wt%Fe made few FeSn2 IMC particles in the solder which does not have considerable effect on mechanical and microstructural properties. 1wt% or 2wt%Bi scattered in the whole of solder without concentration at any position and strengthen solder by a solid solution effect. The surface fracture of solder does not show necking by addition of Bi. Moreover, the solidus temperature of SAC105Fe-2Bi is 214°C, which is 5°C less than SAC105. The addition of 2 wt.% Bi to SC07-Fe decreases the solidus temperature of SC07 from 227.6°C to 223.8°C. After aging at 125 °C for 30 days, UTS (ultimate tensile strength) and yield strength decreased for SAC105 or SC07 by coarsening of IMCs whereas total elongation increased. Scanning electron microscope (FESEM) and energy dispersive X-ray (EDX) indicated that the growth and spheroidization of [Cu6Sn5 and Ag3Sn] for SAC105 or Cu6Sn5 for SC07 after aging controlled by Gibbs-Thomson effect and Ostwald ripening process. Therefore, IMCs and β-Sn grains coarsened. Addition of Bi strengthen solder by scattering in the bulk of SAC105-Fe solder alloy, increased β-Sn and degenerated Cu6Sn5 and Ag3Sn into a chain-like arrangement due to the solid solution and precipitation strengthening effects by Bi in the Sn-rich phase. Partially substitution of Fe in the Cu6Sn5 on the basis of Darken-Gurry ellipse decreased microstructure coarsening rate. UTS, Yield strength, and total elongation are approximately constant for SAC105-Fe-Bi and SC07-Fe-Bi after aging which means stable properties of solder. The nanoindentation results for SC07 and SAC105 solder alloys after addition of Bi and Fe showed a remarkable increase in Er (reduced elastic modulus) and hardness. Wetting angle of SC07 and SAC105 with RMA (rosin mildly activated) flux after addition of Fe and Bi decreased, whereas spreading rate increased.